Language teacher education through social activity: the cultural-social-historical perspective from Brazil to the BRICS - Tanzi Neto, A.; Diegues, U.C.C.; Magalhaes, M.C. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2025)
Abstract only This article analyses how language teacher education in Brazil can be reimagined through the lens of cultural-historical activity theory (CHAT), addressing broader educational challenges shared across BRICS countries for social transformation (Tanzi Neto, 2021). Drawing from a Critical Collaborative Research (PCCol) (Magalhães, 2007; Liberali, 2012) project with five English teachers in Technological Higher Education, the study proposes Social Activity (Liberali, 2009, 2025) as a central curricular principle in the teaching-learning of English for Specific Purposes (ESP) (Hutchinson & Waters, 1987; Valente & Ribeiro, 2023; Diegues, 2025). It seeks to answer the following guiding question: How can language teacher education in Brazil - when grounded in Social Activity and cultural-historical principles - contribute to culturally responsive and socially transformative pedagogical practices within BRICS contexts? To explore this question, a series of reflective workshops was conducted with English teachers at a Technological Faculty in São Paulo (FATEC-SP), Brazil. Based on participants' local realities, the workshops aimed to foster critical pedagogical reflection and collaboratively develop teaching practices that meaningfully respond to the sociocultural contexts of their students. Findings reveal that a reflexive, collaborative approach to teacher education - deeply rooted in teachers' lived experiences and social demands - enhances professional agency, intercultural awareness, and reconfigures teacher identity. The Brazilian case study highlights potential pathways for BRICS nations to resist instrumentalist, neoliberal educational paradigms and to adopt transformative, contextually grounded language education practices. В статье исследуются новые подходы к подготовке преподавателей иностранных языков в Бразилии с использованием положений культурно-исторической теории. В ней рассматриваются более широкие образовательные проблемы, которые объединяют страны БРИКС, и их связь с социальными изменениями. Авторы опираются на проект совместного критического исследования с участием пяти преподавателей английского языка в области технического высшего образования. В рамках этого проекта предлагается использовать концепцию социальной деятельности как главный принцип при обучении английскому языку для специальных целей (например, делового английского или профессионального английского). Цель работы - понять, как обучение преподавателей языков в Бразилии, основанное на принципах социальной деятельности и культурно-исторической теории, может помочь развивать педагогические практики, которые учитывают культурные особенности студентов и способствуют социальным изменениям в странах БРИКС. Для этого авторы провели серию мастер-классов с преподавателями английского языка на Технологическом факультете в Сан-Паулу. В ходе занятий участники обсуждали свои реальные ситуации и вместе разрабатывали методы преподавания, которые успешно отвечают нуждам их студентов и учитывают их культурный контекст. Результаты показали, что подход, основанный на совместной рефлексии и опыте учителей, помогает им стать более инициативными, лучше понимать межкультурные различия и переосмысливать свою профессиональную роль. В целом, кейс из Бразилии показывает возможные пути для стран БРИКС сопротивления навязанным неолиберальным образовательным моделям и внедрения практики обучения иностранным языкам, которые учитывают конкретные социальные и культурные условия.